Formulation of Cassava (Manihot esculenta Crantz) Tuber Extract Gel and Effectiveness Test on Burns in Rabbit (Oryctolagus cuniculus) - Julia Megawati Djamal; Zaenal Fanani; Noor Hidayah; Noor Cholifah (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2021)
Burn is heat transfer in which the source can be direct or indirect contact with fire, electricity, friction chemicals or radiation. It can cause damage of skin tissue even in a state of multisystem injury leading to serious disorders. Systemic effects and mortality caused by burn is generally determined by the extent and depth of affected skin. Cassava (Manihot esculenta Crantz) contains carbohydrates, phosphorus, calcium, vitamin C, vitamin B1, protein and iron. Furthermore, substances contained in cassava are able to give effect to the re-epithelialization of skin damaged cell tissue due to burns. The aim of this study was to find out the cassava tuber extract in gel preparation formulation and the effectiveness of burn healing in rabbits. This study was an experimental study to examine the concentration of cassava tuber extract gel formula which is the most effective in healing superficial burns of degree 4 in male rabbits. From the observations of giving gel preparations once a day by using positive control comparison (Bioplaceton) could be concluded that the extract of cassava provided healing which was not significantly different from the positive control.